2019
DOI: 10.1038/s41598-019-39735-9
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in cancer patients: A nationwide survey in China

Abstract: Cancer patients have a high risk for acute kidney injury (AKI); however, the incidence, severity, and risk factors of malignancy-related AKI (MR-AKI) are unclear. This study aimed to assess MR-AKI risk factors and provide reliable data for AKI prevention, diagnosis, and management in China. This cross-sectional study analysed data from 44 academic and local hospitals in China. AKI patients were identified based on 2 screening criteria: the 2012 Kidney Disease: Improving Global Outcomes-AKI definition and the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…During the prolonged anti-tumor treatment, patients were exposed to higher risks of complications, including AKI. It was reported that about 50.0% of AKI cases and 18.8% of AKI deaths occurred in patients with GI cancer [ 20 ]. Differed from previous studies (2.4%∼35.3%) [ 21–24 ], the AKI incidence of esophagus, stomach, and intestine cancer in this study was 20.5%, 13.9%, and 12.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During the prolonged anti-tumor treatment, patients were exposed to higher risks of complications, including AKI. It was reported that about 50.0% of AKI cases and 18.8% of AKI deaths occurred in patients with GI cancer [ 20 ]. Differed from previous studies (2.4%∼35.3%) [ 21–24 ], the AKI incidence of esophagus, stomach, and intestine cancer in this study was 20.5%, 13.9%, and 12.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies described an overall one-year incidence of AKI in cancer patients between 11% and 20%, with higher risks in patients with hematological cancers [3,4]. Most recently, a study from China that surveyed over 7 million patients demonstrated an incidence of AKI (defined as at least a 50% increase in baseline serum creatinine) at 14 to 20% depending upon the hospital type (community vs. academic, respectively) [5]. Some studies have noted much higher rates of AKI (60%), but are biased with a larger number of critically ill patients with hematological malignancies [6,7].…”
Section: Epidemiologymentioning
confidence: 99%
“…Acute kidney injury (AKI) is a frequent complication among hospitalized patients and is associated with poor clinical outcomes (1,2). Major surgery, sepsis and chemotherapeutic agent use are the leading causes of aKi (3)(4)(5)(6). cisplatin (cP), one of the most commonly used chemotherapeutic drugs, is used to treat a wide spectrum of human malignancies (7).…”
Section: Introductionmentioning
confidence: 99%